Recent Advances in Nanotechnology for Dendritic Cell-Based Immunotherapy - Qian, Chen; Yang, Li-Jun; Cui, Hong (Frontiers in Pharmacology, 2020)
Dendritic cells (DC) as the most important professional antigen presenting cells are determining to cancer immune response in the way of regulating immune activation and tolerance, especially in the initiation stage of specific responses. Manipulation of DCs to enhance specific antitumor immune response consider to be a powerful tool for tumor eradication. Nanotechnology with multifunctional incorporation and spatiotemporal control properties are with intense interests and widely investigated, which provides a fresh insight on improving immune response activity for cancer inhibition even recurrence prevention. In this mini-review, we aim to provide a general view on DC-based immunotherapy, especially inspired by the promising nanotechnology: (1) manipulation or engineering of DCs for adoptive vaccination, (2) modulation of DCs in vivo directly to enhance antigen presentation efficacy, (3) construction of appropriate microenvironment of DCs for activating immune response and priming T cells subsequently. We retrospect the updates of nanotechnology in DC-based immunotherapy and expect to give some insights on the challenges and opportunities of DC-based immunotherapeutics against cancers. Additionally, prospecting the potential of nanotechnology on immune engineering for cancer treatment.